A new tardigrade Doryphoribius maasaimarensis sp. nov. (Eutardigrada: Hypsibiidae) from Kenya - Fontoura, Paulo; Lisi, Oscar; Pilato, Giovanni (Zootaxa, 2013)
A new tardigrade, Doryphoribius maasaimarensis sp. nov., is described from a moss sample collected in Masai Mara Game Reserve, Kenya. The new species is characterized by having a reticulate dorsal cuticle with small tubercles; nine transverse rows of dorsal gibbosities (configuration IX:4-6-4-6-4-6-4-4-2); pharyngeal bulb with two macroplacoids and no microplacoid; claws with short and thin accessory points; small, smooth lunules under the claws. The new species is most similar to Doryphoribius zyxiglobus (Horning, Schuster & Grigarick, 1978). Both exhibit two macroplacoids, similar cuticular pattern and the same configuration of gibbosities. However, in Doryphoribius maasaimarensis sp. nov. the cu-ticular tubercles are less close, buccal tube slightly longer with respect to the body length, more gradual curvature of the buccal tube, different claws shape and thinner accessory points.